2015
DOI: 10.1007/s00586-015-3763-y
|View full text |Cite
|
Sign up to set email alerts
|

The association between symptom severity and physical activity participation in people seeking care for acute low back pain

Abstract: Pain onset causes a significant and immediate decrease in physical activity participation, but this change does not seem to be associated with symptom severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
1
3
0
1
Order By: Relevance
“…Furthermore, they had other symptoms such as high intensity of pain, low quality of pain and life, frequent use of drugs and another characteristic's. Although the correlations were weak, the results corroborate those of other studies [5,[24][25][26], supporting the hypothesis that low back pain patients show a worsening prognosis due to the fear of moving, negative thoughts, and sick leave for low back pain.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, they had other symptoms such as high intensity of pain, low quality of pain and life, frequent use of drugs and another characteristic's. Although the correlations were weak, the results corroborate those of other studies [5,[24][25][26], supporting the hypothesis that low back pain patients show a worsening prognosis due to the fear of moving, negative thoughts, and sick leave for low back pain.…”
Section: Discussionsupporting
confidence: 88%
“…Interestingly, the present PA intervention included not only practical but also educational activities aimed to either increase the overall fitness or reduce a sedentary behaviour possibly affecting the LBP prevalence. In this context, previous observations [37, 43] highlighted the importance of maintaining an active lifestyle through a well-defined and regular PA along with changing of sedentary lifestyle-related unhealthy behaviours to prevent non-specific LBP onset. However, our analyses revealed that there was no significant effect on LBP prevalence when comparing the PA intervention and control groups.…”
Section: Discussionmentioning
confidence: 96%
“…It is known that the non-specific LBP affects multiple aspects of an individual’s life including physical function with limitation of multiple activities, psychological well-being and the ability to work in the general adult population, and particularly among females [2737]. In addition, fear of LBP recurrence may further limit activities [38].…”
Section: Discussionmentioning
confidence: 99%
“…Recovery was defined as being pain-free for at least one month before the follow-up interview [15]. This design has already been successfully used to assess physical activity participation among persons seeking care due to low back pain [22]. Participants were also asked at baseline and follow-up surveys about the presence and intensity of symptoms of depression and anxiety.…”
Section: Methodsmentioning
confidence: 99%